Efficient spatial charge separation and transfer in ultrathin g-C3N4 nanosheets modified with Cu2MoS4 as a noble metal-free co-catalyst for superior visible light-driven photocatalytic water splitting. Issue 15 (11th July 2018) - Zou, Yajun; Shi, Jian-Wen; Ma, Dandan; Fan, Zhaoyang; He, Chi; Cheng, Linhao; Sun, Diankun; Li, Jun; Wang, Zeyan; Niu, Chunming
Abstract : Cu2 MoS4 was employed as a promising non-noble metal co-catalyst to couple with g-C3 N4 for highly efficient water splitting. Abstract : Developing photocatalysts with efficient spatial charge separation and transfer as well as a high light-harvesting ability remains a key challenge. Here, we report a facile in situ process to decorate ultrathin g-C3 N4 nanosheets (NSs) with a co-catalyst, Cu2 MoS4, for photocatalytic water splitting. The as-obtained Cu2 MoS4 /g-C3 N4 exhibits a superior photocatalytic H2 evolution rate of 2170.5 μmol h −1 g −1 under visible light irradiation, which is nearly 677 and 34 times higher than that of bulk g-C3 N4 and g-C3 N4 NSs, respectively, and far exceeds that of most g-C3 N4 catalysts modified with other sulphide co-catalysts reported in the literature, demonstrating that Cu2 MoS4 can serve as a promising non-noble metal co-catalyst to couple with g-C3 N4 for highly efficient photocatalysts. Structural characterization confirms the well-defined morphology of Cu2 MoS4 /g-C3 N4 in which Cu2 MoS4 hollow spheres are uniformly attached on the ultrathin g-C3 N4 NSs with numerous micropores and vacancies. The optical properties indicate that Cu2 MoS4 /g-C3 N4 possesses a superb visible light absorption ability. The photoluminescence spectra, photocurrent response, and electrochemical impedance spectra combine to prove the highly efficient separation and migration of photogenerated electrons and holes. All these factors synergistically enhance the photocatalytic activity of Cu2 MoS4 /g-C3 N4 for photocatalytic water splitting, providing new insights into the rational design of high-performance visible light-driven photocatalysts based on earth-abundant elements.